Incessant pericarditis following the second dose of SARS-CoV-2 mRNA vaccine successfully treated with anakinra: a case report. Issue 9 (13th September 2022) - Conte, C; Princi, G; D'Amario, D; Sanna, T; Pedicino, D; Liuzzo, G
Abstract: Background: The SARS-CoV-2 pandemic has led to the development of the first mRNA vaccines used in humans. These vaccines are well tolerated, safe, and highly effective; however, post-marketing surveillance is revealing potential rare adverse effects. We report a case of incessant pericarditis following administration of the second dose of mRNA-1273 SARS-CoV-2 vaccine, unresponsive to conventional therapy, and successfully treated with anakinra. Case summary: A 30-year-old man presented to the Emergency Department for incessant pericarditis unresponsive to evacuative pericardiocentesis and conventional first-line anti-inflammatory therapy. Given the typical 'inflammatory phenotype' clinically characterized by fever, C-reactive protein (CRP) elevation, and leucocytosis, we decided, in agreement with the rheumatologist team, to avoid glucocorticoid and to administer anakinra. A sudden clinical and echocardiographic improvement was observed, with complete resolution of the symptoms and of the pericardial effusion; similarly, CRP values progressively decreased. The patient was discharged at home; no recurrences of pericarditis were described at clinical and instrumental follow-up made 3 months later. Discussion: Several cases of pericarditis have been described in patients who received the COVID-19 vaccination, especially with the mRNA vaccine that can induce a non-adaptive immunity response against the viral spike protein, triggering cardiac damage for a molecular mimicry mechanism; however, defined pathogenesis of pericarditis associated with mRNA vaccine is still missing. The clinical scenario described is characterized by the typical 'inflammatory phenotype', triggered by a disproportionate and uncontrolled activation of the inflammasome based on an interleukin-1 (IL-1) overproduction. We administered anakinra, an IL-1 blocking drug, with a sharp clinical, echocardiographic and laboratoristic improvement. The complete response observed in this case suggests that vaccine-related pericarditis could be triggered by an auto-inflammatory pathway based on IL-1 overproduction. Further research is, therefore, warranted to determine the mechanisms by which the mRNA vaccine may cause pericarditis in order to choose the most targeted therapy. Graphical Abstract: Graphical abstract